Developmental considerations for ethanolates with regard to stability and physicochemical characterization of efonidipine hydrochloride ethanolate1. Issue 38 (14th October 2015) - Otsuka, M.; Maeno, Y.; Fukami, T.; Inoue, M.; Tagami, T.; Ozeki, T.
<x xml:space="preserve">Abstract</x> Efonidipine hydrochloride ethanolate arranges the chloride ion within a basket-type conformation. This distinctive crystal structure would contribute to the improvement of the API's thermal stability.